2019
DOI: 10.3390/nu11112818
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Triacylglycerol Content and Gene Expression for Triacylglycerol Metabolism, Acyl-Ceramide Synthesis, and Corneocyte Lipid Formation in the Epidermis of Borage Oil Fed Guinea Pigs

Abstract: Triacylglycerol (TAG) metabolism is related to the acyl-ceramide (Cer) synthesis and corneocyte lipid envelope (CLE) formation involved in maintaining the epidermal barrier. Prompted by the recovery of a disrupted epidermal barrier with dietary borage oil (BO: 40.9% linoleic acid (LNA) and 24.0% γ-linolenic acid (GLA)) in essential fatty acid (EFA) deficiency, lipidomic and transcriptome analyses and subsequent quantitative RT-PCR were performed to determine the effects of borage oil (BO) on TAG content and sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The deficiency of enzymes associated with TG hydrolysis or synthesis such as CGI-58 and diacylglycerol acyltransferase2 (DGAT2) has been shown to decrease ω-O-acylCER along with exhibiting skin barrier defects in mice and humans [ 19 , 20 ]. In addition, we have reported that TG containing LA significantly decreased in essential FA deficient guinea pigs with decreased ω-O-acylCER [ 21 , 22 ]. Therefore, it is considered that the LA composition of TG and their amounts may be closely connected with ω-O-acylCER and skin health.…”
Section: Introductionmentioning
confidence: 99%
“…The deficiency of enzymes associated with TG hydrolysis or synthesis such as CGI-58 and diacylglycerol acyltransferase2 (DGAT2) has been shown to decrease ω-O-acylCER along with exhibiting skin barrier defects in mice and humans [ 19 , 20 ]. In addition, we have reported that TG containing LA significantly decreased in essential FA deficient guinea pigs with decreased ω-O-acylCER [ 21 , 22 ]. Therefore, it is considered that the LA composition of TG and their amounts may be closely connected with ω-O-acylCER and skin health.…”
Section: Introductionmentioning
confidence: 99%
“…Olivera-Castillo et al ( 2020) evaluated the bioactive-enriched components found in the sea cucumber (Isostichopus badionotus) body wall that promote anti-inflammatory activity and found that fucosylated chondroitin sulfate, the primary glycosaminoglycan, reduced the expression of critical genes, such as NF-kB, TNFa, iNOS and COX-2, and further lessened the inflammation and tissue damage caused by 12-O-tetradecanoylphorbol-13acetate (TPA) in a mouse ear inflammation model [19]. Lee et al (2019) demonstrated that triacylglycerol (TAG) metabolism is related to the acyl-ceramide (Cer) synthesis and corneocyte lipid envelope (CLE) formation involved in maintaining the epidermal barrier. Their investigation demonstrated that dietary borage oil-enhanced TAG content, the gene expression of TAG metabolism, acyl-Cer synthesis and CLE formation in the epidermis of essential fatty-acid-deficient guinea pigs [20].…”
mentioning
confidence: 99%
“…Lee et al (2019) demonstrated that triacylglycerol (TAG) metabolism is related to the acyl-ceramide (Cer) synthesis and corneocyte lipid envelope (CLE) formation involved in maintaining the epidermal barrier. Their investigation demonstrated that dietary borage oil-enhanced TAG content, the gene expression of TAG metabolism, acyl-Cer synthesis and CLE formation in the epidermis of essential fatty-acid-deficient guinea pigs [20].…”
mentioning
confidence: 99%